2011
DOI: 10.1073/pnas.1019051108
|View full text |Cite
|
Sign up to set email alerts
|

Direct visualization reveals dynamics of a transient intermediate during protein assembly

Abstract: Interactions between proteins underlie numerous biological functions. Theoretical work suggests that protein interactions initiate with formation of transient intermediates that subsequently relax to specific, stable complexes. However, the nature and roles of these transient intermediates have remained elusive. Here, we characterized the global structure, dynamics, and stability of a transient, on-pathway intermediate during complex assembly between the Signal Recognition Particle (SRP) and its receptor. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 42 publications
(26 reference statements)
0
22
0
Order By: Relevance
“…Data analysis of the TR-FRET was done in MATLAB (MathWorks) as previously described (16,47); for specific details see SI Materials and Methods. Critical distance R 0 calculations and analyses of the orientation factor κ 2 effects on the D-A distances are provided in SI Materials and Methods.…”
Section: Preparation Of Lipid Vesicles and Protein-liposome Binding Ementioning
confidence: 99%
“…Data analysis of the TR-FRET was done in MATLAB (MathWorks) as previously described (16,47); for specific details see SI Materials and Methods. Critical distance R 0 calculations and analyses of the orientation factor κ 2 effects on the D-A distances are provided in SI Materials and Methods.…”
Section: Preparation Of Lipid Vesicles and Protein-liposome Binding Ementioning
confidence: 99%
“…We used a series of signal sequence variants described previously (37)(38)(39), in which the hydrophobic core of the pPL signal sequence was replaced by that from phoA, a borderline SRP substrate, or by a combination of leucine and alanine ( Table 1). The Leu/Ala ratio was varied to generate signal sequences with different hydrophobicity (Table 1).…”
Section: Slower Translation Elongation Rescues Translocation Defect Omentioning
confidence: 99%
“…1A). Both SRP and SRP receptor (called FtsY in bacteria) also contain a conserved NG domain, comprised of a GTPase (guanosine 5′-triphosphate hydrolase) G domain and the N domain, whose direct interaction mediates the delivery of cargo to the target membrane.Biophysical analyses (32)(33)(34) showed that membrane targeting is a two-step process in which SRP and FtsY first associate via their N domains to form a transient early intermediate (31,32,35). GTP (guanosine 5′-triphosphate)-driven rearrangements then bring the G domains of both proteins into close contact, giving a stable closed complex (36,37).…”
mentioning
confidence: 99%